PENGEMBANGAN MEDIA PEMBELAJARAN WEBSITE BERBASIS GOOGLE SITES BERBANTUAN KAHOOT! MATERI MENGENAL KARAKTERISTIK WILAYAH KELAS V SDI AL-IKHLAS KABUPATEN TULUNGAGUNG - Oktafiayu, Bella Fransisca; Satria, Aditya Pringga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the limitations of learning media and in the learning process teachers have not used media as a learning intermediary for fifth grade students of SDI Al-Ikhlas Tulungagung Regency. Learning with innovative and creative media is needed to support the learning process of students in order to achieve learning objectives. This study aims to develop learning media based on the Google Sites website assisted by Kahoot! on the material of Recognizing Regional Characteristics of fifth grade students of SDI Al-Ikhlas Tulungagung Regency. The research and development method (Research and Development) with the ADDIE development model consisting of the analysis stage (Analysis), design stage (Design), development stage (Development), implementation stage (Implementation), and evaluation stage (Evaluation). The validation results show that the developed learning media has a high level of validity. Validation by media experts meets the very valid category of 93%, from material experts meets the very valid category of 90%, and the very applicable category from student responses is 92%, the very applicable category from teacher responses is 92.5%. Thus, the Google Sites-based website learning media supported by Kahoot! is declared highly suitable and effective for use in supporting the learning process.